Mycobacterium tuberculosis Prolyl Oligopeptidase Induces In vitro Secretion of Proinflammatory Cytokines by Peritoneal Macrophages - Portugal, Brina; Motta, Flávia N.; Correa, Andre F.; Nolasco, Diego O.; de Almeida, Hugo; Magalhães, Kelly G.; Atta, Ana L. V.; Vieira, Francisco D.; Bastos, Izabela M. D.; Santana, Jaime M. (Frontiers in Microbiology, 2017)
Tuberculosis (TB) is a disease that leads to death over 1 million people per year worldwide and the biological mediators of this pathology are poorly established, preventing the implementation of effective therapies to improve outcomes in TB. Host–bacterium interaction is a key step to TB establishment and the proteases produced by these microorganisms seem to facilitate bacteria invasion, migration and host immune response evasion. We presented, for the first time, the identification, biochemical characterization, molecular dynamics and immunomodulatory properties of a prolyl oligopeptidase (POP) from Mycobacterium tuberculosis (POPMt). POP is a serine protease that hydrolyzes substrates with high specificity for proline residues and has already been characterized as virulence factor in infectious diseases. POPMt reveals catalytic activity upon N-Suc-Gly-Pro-Leu-Gly-Pro-AMC, a recognized POP substrate, with optimal activity at pH 7.5 and 37 °C. The enzyme presents KM and Kcat/KM values of 108 μM and 21.838 mM-1.s-1, respectively. Molecular dynamics showed that POPMt structure is similar to that of others POPs, which consists of a cylindrical architecture divided into an α/β hydrolase catalytic domain and a β-propeller domain. Finally, POPMt was capable of triggering in vitro secretion of proinflammatory cytokines by peritoneal macrophages, an event dependent on POPMt intact structure. Our data suggests that POPMt may contribute to an inflammatory response during M. tuberculosis infection.